كسرة همزة "إن" فى القرآن الكريم سورة البقرة والقصص - Fahmi, Ari Khairurrijal (Al Mah?ra: Jurnal Pendidikan Bahasa Arab, 2018)
The objective of this research is to acquire deep understanding of the "Kasrah Hamzah Inna"  on Alquran Alkareem Albaqarah and Alqashas Epistles,  which consist of 149 verses. The research method used in this study is a descriptive qualitative  method using content analysis of the verses of quran.  The result showed that there are 97 % the "Kasrah" was compulsory, and 3% was uncompulsory. The most verses appear with "Inna" is in the beginning of the kalimah, and after the verb "Qaul" . The 97% of  kasratu inna is a compulsory ,its  divided into five: 1. At the beginning of the sentence amounted to 80 (54%) (and it is divided into 5; a.hakikat it was 13 (16%), b,hokum it was  3 (4%), c.ibtidaiyah it was  12 (15%), d. isti'nafiyyah it was 12 (15%), e. ta'liliyyah  40 (50%)). 2. After the Conjunction it was 1 (1%). 3. After the answer of  oath sentence  it was  1 (1%). 4. After the words amounted to 31 (21%). After the sentence torch circumstances it was  5 (4%). Meanwhile, the position of non compulsory kasratu Hamzah inna was founden  after faa aljazaa,  only 5 times (3%). The results show  that many types of kasrah hamzah inna was founded in  albaqarah and alqashas. Keywords: Kasrah, Hamzah Inna, Alquran, Albaqarah, Alqashas.